Commutative encryption based video encoding technique with high-efficiency & video adaptation capabilities. (17th November 2021) - Sharma, Himanshu; Pareek, Rajneesh; Kumar, Ashutosh; Gour, Nidhi; Sharma, Ravi Shanker; Sharma, Gajanand
Abstract: Before selecting any algorithm to be used for encryption in multimedia application systems, a thorough analysis of the application must be performed to determine what level of security is required for it to work securely. As a result, after determining the necessary security levels, a careful algorithm selection must be made. The algorithm chosen will have an effect on the speed of the coder-decoder-codec. As a result, it is critical to do so before deciding on an encryption method. The algorithms used in this paper improve the overall efficiency of video encoding scheme and it takes less time comparatively with exiting algorithm approach and experiment result show it take less computation time. Proposed algorithm implemented on MATLAB platform and, performance of the proposed algorithms in order to meet the requirement of real-time MPEG decoding, we have optimized the video frame (I Frame, B Frame) with video adaptation capabilities which provide the facility to run the video in any platform. The proposed algorithms are expected to be widely used in the future to provide security for video-on-demand applications and pay-per-view programs. It can be extended to use it as non-MPEG compression schemes such as H.263 for video-conferencing applications.